Types of new service developments initiated by service companies - finance versus non-finance sectors - Aliah Hanim Mohd. Salleh, (Penerbit Universiti Kebangsaan Malaysia, 1994)
This article reports a survey of types of new service developments (NSD'S) practised by top consumer service companies across Europe and USA. For the first time, the research methodology allows compansons to be made between finance and non-finance service sectors, and this is highlighted here. The findings form a descriptive background of a larger study, which incorporates activities in the NSD process and their performance impacts. In sum, NSD'S involve mainly product line extensIOns, repackaging of existing product features and other relatively minor product modifications, rather than truly major innovations. In exploring the reasons for these practices, It was found that "defending market share position" (especially rampant among financial compames) was a common NPD objective underlying these developments. The author calls for a balanced and systematic approach to NSD, which encompasses both true innovation and "innovative iniitation" Developing more new services that offer unique benefits with better overall services quality and value, IS thus called for